SELF-ADJOINT OPERATORS IN KREIN SPACES (Лучшие интеллектуальные исследования, 2025)
Abstract. In this paper, positive, negative, and neutral elements and subspaces are defined using the inner product. The Krein space is defined, and the spectral properties of  self-adjoint operators in this space are studied. The relationships between self-adjoint operators in Hilbert space and  self-adjoint operators in Krein space are explored.